Sandsack Physical Activity Increasing Balance Score in Children with Down Syndrome - Aniek Puspitosari (Jurnal Keterapian Fisik, 2021)
Background: Down syndrome children have motoric and balance problems. Balance problems cause the child to be unable to maintain posture. Physical activity effective to stimulate development motor skills and balance in children. Sandsack physical activity can be applied to optimizing balance in children with down syndrome. The aim of the study was to investigate the effect of sandsack physical activity on balance in children with Down Syndrome. Methods: Quantitative research with pre-experimental research design one group pretest-posttest with a sample size of 13 children with Down syndrome in SLBN Surakarta. Eight sandsack physical activity models are provided in each session. Four sandsack physical activity models per sessions. Balance is measured by sixteen balance test before and after 12 section. The data analysis method uses a paired sample t-test of SPSS. Results: Paired sample t-test results showed that sig. (2-tailed) < 0.05. The increase in the balance score occurred after being given the sandsack physical activity intervention (mean difference of 6.39). Sandsack physical activity intervention have a possitive and significant effect on balance in Down Syndrome children (ρ = 0.001). Most of Down Syndrome children in SLBN Surakarta were male (53.8%). Down Syndrome children in SLBN Surakarta is dominated at the age of 8 and 14 years old (23.1%). BMI score of Down syndrome children in SLBN Surakarta was 15.50 (15.4%). Conclusion: Sandsack physical activity intervention affects the balance in Down Syndrome children. Sandsack physical activity improved balance in children with Down Syndrome and should be applied in conjunction with physical and occupational therapy programs.